Interactions between endoplasmic reticulum stress and extracellular vesicles in multiple diseases - Ye, Jingyao; Liu, Xuehong (Frontiers in Immunology, 2022)
Immune responses can severely perturb endoplasmic reticulum (ER) function. As a protein-folding factory and dynamic calcium storage compartment, the ER plays a pivotal role in resisting pathogens and in the development of autoimmune diseases and various other diseases, including cancer, cardiovascular, neurological, orthopedic, and liver-related diseases, metabolic disorders, etc. In recent years, an increasing number of studies have shown that extracellular vesicles (EVs) play important roles in these conditions, suggesting that cells carry out some physiological functions through EVs. The formation of EVs is dependent on the ER. ER stress, as a state of protein imbalance, is both a cause and consequence of disease. ER stress promotes the transmission of pathological messages to EVs, which are delivered to target cells and lead to disease development. Moreover, EVs can transmit pathological messages to healthy cells, causing ER stress. This paper reviews the biological functions of EVs in disease, as well as the mechanisms underlying interactions between ER stress and EVs in multiple diseases. In addition, the prospects of these interactions for disease treatment are described.